Fee counting method of WIMAX network - JUNXIAN MO (2007)
The related charge method in WIMAX network comprises: A. the charge node adds terminal information into the charge message; and B. the charge server generates charge receipt contained the terminal information according to the former message. When user uses same name/password to access network with different terminal, the server can decides the terminal through the terminal information in charge message for precise charging.